Promdi an Ilokano autobiography - José, F. Sionil (Francisco Sionil) 1924-2022 (Solidaridad Publishing House, 2021)
This collection of personal essays begins with his childhood experiences in his small village of Cabugawan in Rosales, Pangasinan and his memories of his mother who singlehandedly raised him and his siblings.